Transmission dynamics of covid-19 and utility of contact tracing in risk assessment of health-care worker exposure during COVID-19 pandemic - Malathi Murugesan; Padmanaban Venkatesan; Jagadish Ramasamy; Prasanna Samuel; Rajiv Karthik; Winsley Rose; Priscilla Rupali (Wolters Kluwer Medknow Publications, 2022)
Background: In the COVID-19 pandemic, the frontline health-care workers (HCWs) are at increased risk of acquiring infection either through household or workplace exposure. Objectives: To assess the risk of acquiring infection after COVID-19 exposure, we evaluated the effectiveness of a contact tracing assessment to identify the high-risk contacts. Materials and Methods: All HCW who tested COVID-19 positive in July 2020 were interviewed to do risk assessment based on their exposure, advised quarantine, and then followed up on day 14 for development of symptoms of COVID-19. Results: Contact tracing identified 2569 HCW contacts for 422 index positive cases, among which 1642 (63.9%) were contactable for follow-up. Among 1642 contacts, 12.97% developed COVID-19 symptoms within 14 days of the exposure. Household contacts comprising (142 out of 956, 14.9%) had a higher risk of becoming symptomatic than workplace contacts (71 out of 686, 10.3%) ([odds ratio 0.66 (confidence interval 0.49-0.89)]. Of these, 76.6% of the household exposure and 55.4% of significant workplace exposure were tested positive for COVID-19. Conclusions: Based on the risk assessment, we found that a HCW is likely to acquire infection at home rather than at the workplace, and hence, an appropriate quarantine policy can help decrease the transmission and mitigate staff shortage.